Ukraine : Technical Assistance Report-Reforming Management and Oversight of State Assets. (IMF Staff Country Reports; Country Report ;, 2016)
Reform of the SOE sector is a high priority for the government. The recently published 'National Strategy 2020' promises 'state property management reform,' and related reforms in areas such as the organization of government agencies, public procurement, competition policy, and corporate regulation. Reform of the SOE sector also features prominently in the government's 2014 Coalition Agreement. High levels of direct and indirect state support is adding to the significant fiscal risks emanating from SOE sector, a problem that is being exacerbated by the severe economic situation. In addition, weaknesses in the management of the state's investment portfolio need to be addressed to help to significantly increase the value of the government's portfolio of state assets. This will only be possible through improved oversight and governance of the SOE sector.